La construction du francais hexagonal dans trois romans quest Africains (2015)
Sub-Saharan African literature written in French has right from inception been criticized for the adoption of French as its language of expression. Senghor, who is one of the founding fathers of Negritude, defended vehemently why French language imposes itself as a language of expression of a literature, which at the time, addresses itself to the colonizer. The reading of Jean-Marie Adiaffi's La carte d'identite, Ahmadou Kourouma's Les soleils des independances and Adelaide Fassinou's Toute une vie ne suffirait paspour en parler show a rupture with their predecessors and some of their contemporaries vis-h-vis the language of the colonizer. This article as its title indicates, is about the exploration of linguistic and literary procedures employed in the deconstruction of French used in Hexagon, the motivations of the writers and the effects produced on the reader as well as on this literature which is becoming more and more original.